Effect of ankle-foot orthosis on functional mobility and dynamic balance of patients after stroke: Study protocol for a randomized controlled clinical trial. Issue 39 (September 2019) - de Paula, Gabriela Vieira; da Silva, Taís Regina; de Souza, Juli Thomaz; Luvizutto, Gustavo José; Bazan, Silméia Garcia Zanati; Modolo, Gabriel Pinheiro; Winckler, Fernanda Cristina; de Oliveira Antunes, Letícia Cláudia; Martin, Luís Cuadrado; da Costa, Rafael Dalle Molle; Bazan, Rodrigo
Abstract: Introduction: Stroke is the principal cause of impairment in the motor function and gait of adults. One of the resources used in rehabilitation to optimize gait is a prescription of ankle-foot orthosis (AFO), and the most prescribed AFOs are Fixed AFO and Articulated AFO; however, it is not known which of these options is more effective for these individuals. The aim of this study is to evaluate the impact of different types of ankle-foot orthosis functional mobility and dynamic balance in stroke patients. Methods: Prospective randomized controlled clinical trial with 2 parallel groups will be conducted, and the aim is to recruit 50 patients with stroke diagnosis within 1 year, who indicated that they use both types of orthotics, who had a previous Rankin score less than or equal to 3, and who obtained AFO orthosis through the Hospital Clinics at the Botucatu Medical School (HCBMS) São Paulo, Brazil. After a specific evaluation by a physiotherapist, the patient will receive 1 of the AFO types via randomization. After 30 days, the patient will be reevaluated. The primary outcomes will be balance and mobility, which will be evaluated by the Time Up Go Test (TUG) and Tinetti's Scale of Mobility and Balance (TSMB). The secondary outcomes will be quality of life and the levels of anxiety and depression, which will be evaluated with the European (5D) Quality of Life Scale (Euroqol) and Hospital Anxiety and Depression Scale (HADS). Group allocation will be not concealed because the blinding of participants and of therapists that provide intervention is not possible, and all analyses will be based on an intention-to-treat principle. This study was approved by the Human Research Ethics Committee of the São Paulo State University UNESP, number 2.367.953. The results will be published in relevant journal. Discussion: The results of this study will contribute to clinical practice by identifying the type of AFO orthosis that is more suitable for this condition, helping to standardize prescription of these orthoses by professionals, and guiding future research studies on this subject, which is still incompletely defined in the literature. Trial registration: RBR-6SF2VV (March 5, 2018). Abstract : Supplemental Digital Content is available in the text